2016
DOI: 10.1166/jbn.2016.2219
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations for Developing Hyperbranched Polyglycerol Nanoparticles as Systemic Drug Carriers

Abstract: PEGylation is commonly used to increase the plasma residence time of anticancer drug nanocarriers. However, PEGylation may trigger antibody production and lead to accelerated blood clearance in subsequent administrations. Moreover, the presence of PEG shells on nanocarriers may also hamper endosomal escape and decrease drug payload release. To avoid these shortcomings, we synthesized and evaluated a non-PEGylated, hyperbranched polyglycerol nanoparticle (HPG NP) with a hydrophobic core and a hydrophilic HPG sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…The degrees of hydrophobicity of the unmodified HPG NPs were measured and reported before with pyrene fluorescence probe method. 16 The orders of hydrophobicity of unmodified and Alexa 488-conjugated HPG NPs remain the same. The results of these complementary methods revealed that the conjugation of the Alexa dye did not influence the order of hydrophobicity of the HPG NPs.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The degrees of hydrophobicity of the unmodified HPG NPs were measured and reported before with pyrene fluorescence probe method. 16 The orders of hydrophobicity of unmodified and Alexa 488-conjugated HPG NPs remain the same. The results of these complementary methods revealed that the conjugation of the Alexa dye did not influence the order of hydrophobicity of the HPG NPs.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The syntheses and physicochemical characterization of these HPG NPs were reported previously. 16 HPG-C 10 -HPG is a nanoparticle that contains a hydrophobic core of C10 alkyl chains with a hydrophilic HPG shell. HPG-C 10 -PEG is similar to HPG-C 10 -HPG, except that the polyethylene glycol (PEG) shell was grafted onto the surface of the nanoparticle.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPG ( M n = 6659, M w / M n = 1.3) was prepared in our laboratory, according to the literature. 34 , 35 The hyperbranched polyglycerols were synthesized by anionic ring-opening polymerization, and the monomers in the reactions should be added very slowly to ensure low polydispersity.…”
Section: Methodsmentioning
confidence: 99%
“…Among such highly branched macromolecules, hyperbranched polyglycerol (HbPG) with average diameter in the few nanometer range (~2-20 nm) and with both chain end and pendant hydroxyl functionalities offers a variety of new derivatization processes to obtain materials with advantageous application possibilities, ranging from biomedicine to nanotechnologies and large scale commodities as well [9][10][11][12][13][14][15][16][17][18]. HbPG is a polyether polyol, which has favorable properties, namely low cytotoxicity, biocompatibility, water solubility and low viscosity [19][20][21].…”
Section: Introductionmentioning
confidence: 99%